Study of Quantitative and Dynamics Polymer Particle Tracking: Methods for studying conformational dynamics of flexible polymer molecules (Journal of Advances and Scholarly Researches in Allied Education, 2012)
We present a new method foranalyzing the dynamics of conformational fluctuations of individual flexiblepolymer molecules. In single-particle tracking (SPT), one end of the polymermolecule is tethered to an immobile substratum. A microsphere attached to theother end serves as an optical marker. The conformational fluctuations of thepolymer molecule can be measured by optical microscopy via the motion of themicrosphere. The bead-and-spring theory for polymer dynamics is furtherdeveloped to account for the microsphere, and together the measurement and thetheory yield quantitative information about molecular conformations anddynamics under nonperturbing conditions. Applying the method to measurementscarried out on DNA molecules provides information complementary to recentstudies of single DNA molecules under extensional force. Combining highprecision measurements with the theoretical analysis presented here creates apowerful tool for studying conformational dynamics of biological and syntheticmacromolecules at the single-molecule level.